FROM TRASH TO TREASURE: TINJAUAN METODE PRE-TREATMENT PADA LIMBAH RUMAH TANGGA DAN PENIILAIANNYA TERHADAP ANALISIS SIKLUS HDUP - Mahdiyyah Naurah Salsabila; Florentina Ratna Eris Nanda; Salwa Permata A’yun; Aisyah Lala Aprillia; Denny Oktavina Radianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Waste pollution has become a trending topic which involves pollution of the ecology, ecosystem, and requires certain processes. Solutions regarding this have changed along with technological developments in converting waste or rubbish into high-value products. Recovery of this waste requires various methods ranging from chemical, thermal, thermochemical, physical, biological and microbiological methods. The use and application of the method in industry has been proven and explained in detail. In this article, a systematic literature review method is used using predetermined keywords so that 46 references are obtained and discussed in the results and discussion section. Data is sorted and created into several dimensions. The largest composition of waste is dominated by household waste, based on its source, and organic waste such as food waste, based on its composition. The pre-treatment methods given to waste also have their own advantages and limitations. In addition, the life cycle assessment of various methods also shows the impact of each pre-treatment on the environment, social sustainability and a better environment. Therefore, it can be concluded that the government must determine the latest methods in managing this waste by considering its impact on ecology, ecosystems and the environment.